Realisasi Konsep Maqosid Shariah Index Perbankan Syariah di Indonesia - Rahmat Hidayat (Ecobankers : Journal of Economy and Banking, 2020)
This research proves that the concept of Maqasid Shari'ah can be a method of evaluating social-based performance of Islamic banking Islamic law in Indonesia with three measurement aspects namely Tahdhib al-Fard (Individual Education), Iqamat al-'Adl (creating justice) and Jalb al-Maslahah ( creating the benefit of the Ummah). Data analysis using descriptive quantitative with the nature of case study research. The results of this study indicate that the achievement of the concept of Maqasid Shari'ah is divided into three aspects, namely aspects of Tahdhib al-Fard (educating individuals), Iqamat al-'Adl (building justice), Jalb al-Maslahah (creating public interest) Islamic banking in Indonesia it cannot be realized properly, this is due to the lack of the role of Islamic banking in improving the quality of Human Resources (SDI) as well as public education, inequality of murabaha financing instruments with mudharabah financing instruments, musharaka which is wide enough, to the low allocation of zakat funds. Keywords: content; formatting; article. Abstrak Penelitian ini membuktikan konsep Maqasid Shari’ah dapat menjadi matode evaluasi kinerja berbasis sosial hukum islam perbankan syariah di Indonesia dengan tiga aspek pengukuran yaitu Tahdhib al-Fard (Pendidikan Individu), Iqamat al-‘Adl (menciptakan keadilan) dan Jalb al-Maslahah (menciptakan kemaslahatan ummat). Analisis data menggunakan kuantitatif deskriptif dengan sifat penelitian studi kasus. Hasil penelitian ini menunjukkan bahwa pencapaian konsep Maqasid Shari’ah yang terbagi dalam tiga aspek yaitu aspek Tahdhib al-Fard (mendidik individu), Iqamat al-‘Adl (membangun keadilan), Jalb al-Maslahah (menciptakan kepentingan umum) perbankan syariah di Indonesia belum dapat direalisasikan dengan baik, hal tersebut dikarenakan kurangnya peran perbankan syariah dalam meningkatkan kualitas Sumber Daya Insani (SDI) serta pendidikan masyarakat, ketimpangan instrumen pembiayaan murabahah dengan instrumen pembiayaan mudharabah, musyarakah yang cukup lebar, hingga rendahnya alokasi dana zakat. Kata Kunci: isi; format; artikel.